Graffiti: A New Dimension in School Discipline in Secondary Schools in Kenya - Luvaso, Aliva (Machakos University, 2019)
Graffiti is writing or drawings made on a wall or other surface, usually without permission and within public view. Graffiti ranges from simple written words to elaborate wall paintings, and it has existed since ancient times, with examples dating back to ancient Egypt, ancient Greece, and the Roman Empire. In modern times, paint and marker pens have become the most commonly used graffiti materials. In most countries, marking or painting property without the property owner's permission is considered defacement and vandalism, which is a punishable crime. Many students in our public secondary schools have embraced the use of graffiti in books, buildings and even on their bodies which is also done by our various worldly sportspeople, heroes and heroines in various fields. The kind of graffiti the youth draw is a replica of who they are. This literary paper investigates the various types of graffiti drawn by our secondary school students, interpret their meanings and determine their effects on students’ performance and discipline. This paper is guided by Behaviour Modification theory by B.F. Skinner on “how our voluntary actions are influenced by what happens to us immediately after we perform a given act”. Controversies that surround graffiti continue to create disagreement amongst city officials, law enforcement, school administrators and writers who wish to display and appreciate work in public locations. This paper finds that many students enjoy the use of graffiti but they are not so specific about the meaning they are portraying. The paper concludes that there is need to develop guidelines especially on use of graffiti in our schools. Interventions are needed which include all stake holders to ensure change is effected and lastly sensitization programs need to be put in place to help the youth understand the effects of graffiti
Keywords: Graffiti; School discipline; Dimension; Academic performance; Secondary school